"Institutions, production, and working life/edited by Geoffrey Wood and Phil James" - "Wood, Geoffrey(ed.)" (Oxford, 2006)
What is the link between working life and the nature of production on the one hand, and the changing organization of the firms and institutions in which work and production take place? In this book leading socio-economic theorists analyze how these have changed over the last two decades.
Keywords: Economic development